The moon and sixpence - Maugham, W. Somerset (William Somerset), 1874-1965. (New York : Vintage Intertnational, 2000)
Reprint of a 1919 novel in which Charles Strickland rebels against his life as a London stockbroker and decides to abandon civilization and his family to pursue a career as a painter in the South Pacific.
Originally published in 1919.
Adult
Keywords: Painters -- Fiction; Painters -- Fiction; Psychological fiction; England -- Fiction; Tahiti -- Fiction; England -- Fiction; Tahiti -- Fiction; Psychological fiction